The Effect of Tax Reform and Tax Auditing on Its Performance (Studies in East Java Regional Office of the Directorate General of Taxes III Malang) - Kariyoto, Kariyoto (International Journal of Social and Local Economic Governance, 2016)
This study aims to prove empirically the effect of tax reform and tax audit on the performance of taxation. This study is expected to enrich and to complement the repertoire science in the field of public sector accounting especially on the development tax reform, tax audits, and empowerment of performances. This research population is account representatives spread across the Regional Office of Directorate General of Taxation III of East Java as much as 234 account representatives. Samples were taken as many as 124. Respondents who participated were 124 account representatives. The sampling method used was a proportional stratified random sampling of 50% and data analysis using SEM (Structural Equation Modelling). The main discovery of this study provides information that the role of tax reform and tax audit in improving the performance of tax is proved to be effective.Keywords: reform, audit, and performance of taxation